The Potential of Active Metabolites in Cruciferous Vegetables to Inhibit the Growth of Cancer Cells - Tesya Agustin (Jurnal Penelitian Perawat Profesional, 2020)
Cancer is a malignant disease caused by the uncoordinated abnormal cells growth in body tissues. Cancer is the most common cancer case that causes deaths in Indonesia. Various therapeutic approaches have been developed but the toxicity from the effects of cancer treatment has a negative impact to the patients. Researchers are intensively conducting research on food products that contain health benefits, one of them is cruciferous vegetables. Cruciferous vegetables are a type of food that have a high nutritional content and health benefits, both in preventing and treating a disease. The compounds contained in it are able to fight cancer cells with minimal side effects. The purpose of writing this article is to determine the role of cruciferous vegetables as an inhibitor of cancer cell growth in order to be used in prevention and treatment of cancer. The method used is a literature review with the inclusion criteria of international scientific journals in the last ten years (2011-2020) accessed through a trusted site. The search results on the NCBI, Elsevier, Pubmed, and other sites, 1225 articles obtained that match keywords in the 2011-2020 period and only 31 articles were considered relevant. The analysis was carried out using the systematic literature review by identifying, examining, assessing, and presenting it. The results obtained were that the active metabolites in cruciferous vegetables in the form of sulforafan, erucine, and indole-3-carbinol had an effect on cancer cells. These active metabolites are able to fight cancer cells with their effective mechanism of action so that cruciferous vegetables have the potential to inhibit the growth of cancer cells.